DETERMINATION OF THE FRACTAL DIMENSION OF QUARTZ SAND PARTI- CLES FROM THE TASH-KUMYR AND OZGUR DEPOSITS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article is devoted to the analysis of the morphology of quartz sands using newmethods of fractal geometry. The object of the study is the quartz sands of the Tash-Kumyr andOzgur deposits, as well as the subject of the study of determining the fractal dimensions of thesesands. And also determination of the dispersed composition of quartz sands of the same deposits.A computer program has been created to create a logarithmic grid with the help of which aparameter (angle tangent) can be determined to find the fractal size of sand particles. Based on thetheory of self-similarity, a model has been created for calculating the fractal dimension of quartzsand particles from the Tash-Kumyr and Ozgur deposits.It was revealed that the fractal dimensionof particles within the range of 0-0.1mm of quartz sand of the Tash-Kumyr deposit exceeds thedimension of quartz sand of the Ozgur deposit by 4%
Keywords: Quartz sand, fractal dimension, dispersion, logarithmic grid, counting the number of cells.